ฟ้อนเล็บ : คณะช่างฟ้อนอาวุโสวัดพระสิงห์วรมหาวิหาร จังหวัดเชียงใหม่ - สรายุทธ อ่องแสงทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This thesis aims at studying the history concept and dance patterns of senior dancers at Wat Pra Sing temple in Chiangmai during 1960-2007 Research methodology includes documentary, interviewings dancers and scholars, observing actval performances and VCD,and researcher’s training with the senior dancers. The research finds that dance plays a very important part in many Chiangmai traditional festivals Nowsaday, dance is used to promote tourism among which Fon Leb or nail dance is the most popular, Fon Leb was probably began around 1920’s and being performed by four major groups today First is the dancers who belong to the northern royql families twho dance on special occasicns such as welcoming the King and Queen to Chiangmai. Second is the school girls who dance for their school functions. Third is the commercial groups who entertain tourists and perform for business events. Forth is the dancers belonging to a particular Buddhist temples such as Wat Pra Sing group. This group comprises 4 senior dancers perform occasionally at Wat Pra Sing temple fairs and some special fairs elsewhere They dress in traditional Chiangmai costume wearing long brass nails on every finger except the thumbs. Theg dance with a special kind of music ensemble called "Tueng N0ng". Their dance style is a combination of those from the ancient court of Chiangmai and from the northern folk dance. There are 15 dance positions and 3 floor patterns. They dance on 5 counts instead of 7 counts as commonly practice by other groups. This dance groups and their special dance style are declining since there is transmission of knowledge to younger generation. There should be some ways to preserve this ancient and valueless dance form.